Teachers’ Attitudes Towards the Application of the Experimental Method in Teaching Nature and Society - Župić, Ajdina A. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Teaching nature and society should encompass a combination of different methods that encourage students to engage in independent research, critical thinking, and logical reasoning. The experimental method contributes to the development of students’ learning in an effective way by providing opportunities for them to express their opinions, make assumptions, conduct experiments, actively observe phenomena and processes, record their observations, think critically, and draw conclusions independently. The aim of this paper was to examine and determine teachers’ attitudes and opinions regarding the use and significance of the experimental method within the subjects Nature and Society and The World Around Us. The research was conducted in the Republic of Serbia in 2025 and included 103 teachers. The results showed that teachers recognize the importance and benefits of applying the experimental method for the development of students’ personality, and that there is no statistically significant difference in their attitudes regarding years of work experience or the type of settlement in which the school is located. The conclusions of the paper indicate that teachers are willing to apply this method in their teaching practice but face obstacles in its implementation, particularly due to the lack of equipment in schools. Adequate support provided to teachers may contribute to improving the application of the experimental method in practice.
Keywords: experimental method; contemporary teaching; teaching nature and society; teachers’ attitudes